Impact of Covid-19 on the economic development of microentrepreneurs in Jipijapa - Baque, Erick (2021)
Micro-enterprises have a singular importance, due to their capacity to generate employment and income, useful for the productive device to be able to boost economic activity, in Ecuador and in particular in Jipijapa. The impact of COVID 19. Economic systems are affected by this pandemic and the Latin American region is considered the hardest hit of all. In this research, it is proposed to carry out an update of the knowledge, to perceive what is the situation that the microentrepreneurs of the city of Jipijapa, Ecuador present, regarding the impact of COVID 19, in terms of their strategic planning. For this purpose, an exploratory, descriptive and documentary research is developed, supported by a bibliometric analysis, oriented to the analysis of scientific articles, field research results are presented to 250 microentrepreneurs of the Jipijapa canton, of the Manabí province, in the interests of to have a real vision of the problems faced by microentrepreneurs, useful in raising awareness of the need to propose strategies for their strengthening, innovation and scope of the main characteristics that are necessary to create competitive advantages and position themselves in the market.